What causes the positive price-turnover correlation in European housing markets? - Martijn I. Dröes; Marc K. Francke (Tinbergen Institute, 2016)
This paper examines what determines the correlation between prices and turnover in European housing markets. Using a panel vector autoregressive model, we find that there is a particularly strong feedback mechanism between prices and turnover. Momentum effects are another important reason why prices and turnover are correlated. Common underlying factors, such as GDP and interest rates, also explain part of the price-turnover correlation. The results in this paper imply that, to understand price and turnover dynamics, it is important to model prices and turnover as two interdependent processes. Ignoring this interdependency results in a considerable bias in the coefficient estimates of both price and turnover models.
Keywords: E02; R31; O18; 330; price-turnover relationship; feedback; momentum effects; credit constraints; nominal loss aversion